The concept of Waqf and development of infrastructure of Waqf in Selangor / Ahmad Farhan Mohd Hassan - Mohd Hassan, Ahmad Farhan (Academy of Contemporary Islamic Studies (ACIS), 2016)
The Waqf is one of the most important asset in the Islamic economy community, its growth with the creation of civilization in the world. Waqf also involve directly in arrangement of living regarding society or community through mosque, school, university and other. Waqf will be great if there is good management and strategic system applying and using updating new information and management of property, so the investment of the asset in an economy in Islamic approaching can be expand and smooth in progress regarding social guarantee Furthermore, the Waqf is an instrument of beneficiaries which help individuals and not just that, but also give a great impact to a whole community. As we can see Waqf properties could immovable or movable. Commonly, it’s referred to lands or houses which are usually used for the settlement of the beneficiary's name or intended by the donor for good act. As for individual or community, we must take a look the useful of Waqf and need to understand the concept of Waqf and its management because it give a benefit and idiosyncrasy not just our self on physical condition, but also an effect on spiritual manner which as we can see the terms of Hablum-Minaallah and Hablum-Minanass.